BIBLIOMETRIC ANALYSIS FROM LOCAL INSTRUCTION THEORY RESEARCH - Edi Supriyadi; Jarnawi Afgani Dahlan; Darhim Darhim; Dadang Juandi (Journal on Mathematics Education Research (J-MER), 2022)
A field known as bibliometrics is one that allows for the evaluation of different scientific publications using a variety of different indicators. The purpose of this research is to carry out a bibliometric analysis of the amount of work that has been done in the field of local instruction theory between the years 2009 and 2020. All of the journal articles that were retrieved from the Scopus database between the years 2009 and 2020 were incorporated. As bibliographic indicators, we used things like the number of publications, the most productive institutions, the type of collaboration, the most productive countries, the most cited papers, and authors who had the highest overall academic production. It is then sent to the SciVal tools in order to undergo analysis. The research on local teaching theory was drawn from a total of 29 published publications, with 50 different writers contributing to the collection of 41 citations. The most documents have been produced in Indonesia, which is the world's largest country. The institution that has the biggest scientific influence and production is Sriwijaya University, which also has the highest scientific production. Ratu Ilma Indra Putri is the author who has had the most manuscripts published throughout the course of her career. Last but not least, the majority of articles involve collaboration between institutions. Local instruction theory research is still new and hasn't made a global impact. Academics can submit relevant article citations, putting them at the forefront of the latest research.